Prevalence and Molecular Detection of Toxigenic Genes of Bacillus cereus in Rice-Based Street Foods in Tasikmalaya, Indonesia - Maerani Maerani; Mufti Ghaffar; Fadhiya Munggarani; Dina Aulia Nuraeni; Pandu Legawa Ismaya; Hadi Yusuf Faturochman (AgriHealth: Journal of Agri-food, Nutrition and Public Health, 2026)
Bacillus cereus is a spore-forming foodborne pathogen frequently associated with rice-based foods and capable of causing emetic and diarrheal illnesses through the production of heat-stable and heat-labile toxins. This study investigated the prevalence, contamination levels, and toxigenic gene profiles of B. cereus in rice-based street foods. A total of 12 samples, including fried rice, chicken porridge, and nasi kuning, were collected from street vendors in Kahuripan Sub-district, Tasikmalaya, Indonesia. Presumptive B. cereus was isolated using mannitol yolk polymyxin agar (MYPA) as a selective medium and confirmed biochemically and molecularly by PCR targeting the gyrB gene. Toxigenic potential isolate was evaluated by detecting the nheA, hblD, cytK, entFM, and ces genes. Presumptive B. cereus was detected in 91.67% (11/12) of samples, while molecular confirmation identified gyrB-positive isolates in 42% (5/12) of samples, originating from fried rice and chicken porridge. No significant association was found between food type and gyrB detection (p > 0.05). Contamination levels ranged from < 1.5 × 10¹ to 2.95 × 10⁶ CFU g-1. All confirmed isolates harbored at least one toxigenic gene, with nheA being the most prevalent (80%), followed by cytK (60%), entFM (40%), ces (40%), and hblD (20%). Notably, one of the fried rice isolates carried all 5 toxin-related genes, indicating a high virulence potential. These findings demonstrate that rice-based street foods in Tasikmalaya may pose a significant public health risk due to contamination with toxigenic B. cereus. Enhanced hygiene practices, strict temperature control, and molecular surveillance are essential to reduce the risk of foodborne illness associated with street-vended rice products.